Corpus callosum hypogenesis with interhemispheric cyst: a case report - Das, Abhishek; Das, Aditi; Chakrabartty, Debakumar (International Journal of Research in Medical Sciences, 2017)
Agenesis or hypogenesis of Corpus callosum with interhemispheric cyst is a rare entity. Origin of interhemispheric cyst is controversial. These cysts may be Arachnoid cyst, neuroepithelial cyst, or extension of lateral or third ventricles. Here we describe a case of Corpus callosal hypogenesis with an interhemispheric cyst. Associated aqueductal stenosis and schizencephaly is also present. Interhemispheric cyst is communicating with lateral ventricle and the cyst has MRI signal intensity similar to CSF. This case supports the theory that the interhemispheric cyst is an ependymal cyst and is consequence of increased intraventricular pressure due to aqueductal stenosis.